Analisis Kemampuan Literasi Sosial Siswa Kelas IV Sekolah Dasar - Lintang Ayu Fitriyani; Erni Suharini; Udi Utomo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to describe students' social literacy abilities in terms of social literacy indicators, namely understanding oneself, understanding and managing emotions, understanding social situations, and establishing relationships. This research is a descriptive research, by analyzing student test results. The research subjects consisted of 30 fourth grade students at SDN 1 Mangkujayan. The results of the study showed that the social literacy skills of fourth grade students at SDN 1 Mangkujayan regarding kingdoms in the archipelago were still in the very low category, namely getting a percentage of 51%. Special teaching materials are needed for students who can increase students' social sensitivity so that they can increase social literacy in students. Keyword: social literacy, socil education, history, local wisdom